2019
DOI: 10.4103/ajns.ajns_236_18
|View full text |Cite
|
Sign up to set email alerts
|

The utility of cervical spine bracing as a postoperative adjunct to single-level anterior cervical spine surgery

Abstract: Background Context: Use of cervical bracing/collar subsequent to anterior cervical spine discectomy and fusion (ACDF) is variable. Outcomes data regarding bracing after ACDF are limited. Purpose: The purpose of the study is to study the impact of bracing on short-term outcomes related to safety, quality of care, and direct costs in single-level ACDF. Study Design/Setting: This retrospective cohort analysis of all consecutive patients ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Bracing following cervical procedures can even become harmful as cervical collars have been associated with pain, muscle atrophy, decubitus ulceration, breathing or swallowing discomfort, and difficulty driving [ 99 ]. Cervical collars can be expensive, ranging in price from USD25 to USD750, contributing to their questionable use [ 96 , 100 ]. With respect to lumbar procedures, the American Association of Neurological Surgeons (AANS) specifically recommends against the use of bracing postoperatively due to their lower efficacy rating [ 98 , 101 ].…”
Section: Postoperative Spinal Bracingmentioning
confidence: 99%
See 2 more Smart Citations
“…Bracing following cervical procedures can even become harmful as cervical collars have been associated with pain, muscle atrophy, decubitus ulceration, breathing or swallowing discomfort, and difficulty driving [ 99 ]. Cervical collars can be expensive, ranging in price from USD25 to USD750, contributing to their questionable use [ 96 , 100 ]. With respect to lumbar procedures, the American Association of Neurological Surgeons (AANS) specifically recommends against the use of bracing postoperatively due to their lower efficacy rating [ 98 , 101 ].…”
Section: Postoperative Spinal Bracingmentioning
confidence: 99%
“…With respect to lumbar procedures, the American Association of Neurological Surgeons (AANS) specifically recommends against the use of bracing postoperatively due to their lower efficacy rating [ 98 , 101 ]. Decrease in the perceived effectiveness of bracing following spine surgery may result from recent improvements in surgical techniques and instruments used in spinal procedures such as anterior cervical discectomy and fusion (ACDF) [ 98 , 100 ]. With improved technology and technique, high levels of internal spinal stabilization are achieved with surgery alone, rendering additional postoperative bracing redundant.…”
Section: Postoperative Spinal Bracingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, reviewing the literature, there is scarce data supporting these hypotheses. Caplan et al [ 3 , 4 ] examined patients who underwent single and multilevel anterior cervical discectomy and fusion (ACDF) showed that there is no superiority of those who used cervical collars over the controls. Moreover, Overley et al [ 5 ] showed no advantage in wearing a cervical brace following one- or two-level ACDF in a prospective randomized study.…”
Section: Introductionmentioning
confidence: 99%
“…Another concern for health systems is the cost effectiveness of cervical collar use and its impact on the global burden of diseases. However, there are some reports that cervical collar administration after ACDF surgery leads to a lower hospital stay length with no significant effect on the total cost of the patient [ 4 ].…”
Section: Introductionmentioning
confidence: 99%